Morpho-anatomical Study of 100 Tomato Lines - Maiti, Ratikanta; Rajkumar, D.; Jagan; Vidyasagar, P. (International Journal of Bio-resource and Stress Management, 2014)
A study has been undertaken of 100 genotypes of tomato grown in polyhouse during summer (April-May 2012) for general morphological and anatomical characters of leaves of one hundred tomato genotypes and its possible relation with drought and heat stress tolerance and resistance to insects probably tospo virus resistance. There existed a lot of variability of leaf morphology, and its anatomy. It is concluded that lines having thick leaves & medium to high density of trichomes, minimum wilting, high number of flowers, may be considered for heat stress and drought tolerance. Lines with high density of trichomes are probably tospovirus resistance which could be confirmed in rainy season in the field. Genotypes with open canopy, thick petiole, and thick leaves expected to be drought resistance. Anatomically compact long palisade tissue and more number of collenchyma layers in petioles offer drought resistance. Five genotypes were selected for good pollen viability. More than thirty genotypes possessed high trichome density which may be expected for TLC and Tospo virus resistance. These lines may be evaluated for TLC and Tospo virus resistance at hotspots. These lines are also expected to be tolerant to drought.